The Resilience Program: preliminary evaluation of a mentalization-based education program - Bak, Poul L.; Midgley, Nick; Zhu, Jin L.; Wistoft, Karen; Obel, Carsten (Frontiers in Psychology, 2015)
In order to manage with the burden of mental health problems in the world we need to develop cost-effective and safe preventive interventions. Education about resilience to support the ability to cope with life challenges in general, may be a useful strategy. We consider the concepts of Theory of Mind and Mentalization to be relevant in this context. In this paper we describe a simple modular intervention program based on these concepts which can be tailored to specific needs and situations in individual therapy as well as group levels. The program has shown promising results in pilot studies and is now tested in controlled trials in settings such as schools and educational institutions, adults diagnosed with ADHD and children in foster care.